Visual Outcomes after Endoscopic Pituitary Surgery in Patients Presenting with Preoperative Visual Deficits - Fredes, Felipe; Undurraga, Gabriel; Rojas, Pablo; Constanzo, Felipe; Lazcano, Carolina; Pinto, Jaime; Schmidt, Thomas (Journal of Neurological Surgery Part B: Skull Base, 2017)
Introduction Pituitary adenomas represent 15% of primary brain tumors. Visual disturbance is a common clinical manifestation of these neoplasms due, among other factors, to local mass effect on the optic system.Objective To evaluate changes of the visual fields in patients undergoing endoscopic endonasal approach (EEA) for pituitary adenomas and to find predictive factors for successful visual field outcome.Material and Methods This is a cross-sectional study. A review was conducted of medical records of consecutive patients with tumors of the sellar region undergoing EEA between January 2008 and December 2012 at the Skull Base Unit of Guillermo Grant Benavente Hospital, University of Concepción, Concepción, Chile, and who had undergone pre- and postoperative visual field evaluation.Results A total of 35 patients, with a mean age of 50.2 years, fulfilled the inclusion criteria. All patients had objective visual field disturbances before the surgery. Following surgery, 25 patients (71.4%) had favorable outcomes, whereas 8 (22.8%) had no change and 2 (5.8%) had an unfavorable outcome. Complete tumor removal was associated with a better visual outcome than those obtained after a subtotal removal.Discussion The EEA for pituitary tumors is particularly effective for visual field disturbances, with reported improvement rates ranging from 50 to 90%. Our series show similar results, with a 71.4% improvement of visual field disturbances.Conclusion This study adds further evidence to the current belief that EEA for pituitary adenomas is a safe and effective technique to improve visual field alterations. Complete removal of the tumor during surgery seems to be a predictive factor for a good visual outcome.
Keywords: pituitary; endoscopic endonasal approach; visual field; optic nerve; optic chiasm